Anthropogene Änderungen des Strahlungshaushalts der Erdoberfläche.: Zur Problematik der Rekonstruktion vorzeitlicher Strahlungsklimate in Mitteleuropa - Kessler, Albrecht (ERDKUNDE, 1985)
Problems are discussed which result from the reconstruction of the radiation budget of the earth’s surface of postglacial times in Middle Europe. Data of measured net radiation components of a grass surface and of a pine stand are presented. The importance of cloud amount on the budget components is referred to.